A MULTI-POINT BOUNDARY PROBLEM FOR A SIMPLE DIFFERENTIAL EQUATION OF A FIRST ORDER LINEAR (Scientific journal of the Fergana State University, 2023)
In this article, explaining a method of solving the problem for a multi-point boundary problem for a simple differential equation of a first order linear s given.